If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4-6x-2=9
We move all terms to the left:
3x-4-6x-2-(9)=0
We add all the numbers together, and all the variables
-3x-15=0
We move all terms containing x to the left, all other terms to the right
-3x=15
x=15/-3
x=-5
| (x-5)^2-49=0 | | 6(x+4)=2(2x-1) | | 3(x-2)+7x=1/2(6x2) | | 24x+4+2x=3(10x-1)=2 | | –4m+7=–3m−2 | | x(x-5)^2-49=0 | | 7r^2+17r+6=0 | | Y=2x^-16x+29.Y=5 | | -6=f/7 | | 24x+4+2x=3(10x-1))=2 | | 6(x+4)=2(2x−1) | | 15+2d=d | | 81=3x+45 | | c/3+1/3=2 | | 6=7+n/6 | | 4=81y | | 3x–10x+5=5x+17(5A/R) | | Y=2x^-16x+29 | | 7-5=4x | | 1+19r=15+17r | | 30+90-4+8x=180 | | 2x+2x-10=180 | | 2x-3+57+2x=180 | | 19-12n=19-18n-7n | | 40x+44=38x+44 | | 4(5m-6)=16 | | 3c–9=0 | | -2(3r-4)+2=16 | | s-39=-29 | | 2b/3+1=3 | | 18=-2(x-5) | | 23y+10=38 |